2002
DOI: 10.1113/jphysiol.2002.023408
|View full text |Cite
|
Sign up to set email alerts
|

Opioid‐resistant respiratory pathway from the preinspiratory neurones to abdominal muscles: in vivo and in vitro study in the newborn rat

Abstract: Journal of Physiologytransmitting it to L1 motoneurones, by using the in vitro brainstem-spinal cord preparation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
163
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 159 publications
(183 citation statements)
references
References 46 publications
18
163
1
1
Order By: Relevance
“…These data provide evidence of a second rhythm generator (expiratory), which is only expressed with depression of the inspiratory rhythm generator. This expiratory rhythm generator is rostral to the pre-BötzC area ventrolateral to the rostral Bötzinger complex and/or in the parafacial region (4,8,14,17). In goats during the tachypneic period following IA injections, rhythmic abdominal muscle activity was clearly present, and it was characteristically 180°o ut of phase with diaphragm activity.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…These data provide evidence of a second rhythm generator (expiratory), which is only expressed with depression of the inspiratory rhythm generator. This expiratory rhythm generator is rostral to the pre-BötzC area ventrolateral to the rostral Bötzinger complex and/or in the parafacial region (4,8,14,17). In goats during the tachypneic period following IA injections, rhythmic abdominal muscle activity was clearly present, and it was characteristically 180°o ut of phase with diaphragm activity.…”
Section: Discussionmentioning
confidence: 95%
“…Janczewski et al (8) and Mellen et al (14) have recently demonstrated expression of rhythmic expiratory muscle respiratoryrelated activity following a -opioid-induced depression of pre-BötzC inspiratory neurons. These data provide evidence of a second rhythm generator (expiratory), which is only expressed with depression of the inspiratory rhythm generator.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations